2013
DOI: 10.1089/jmf.2012.0083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Barley Flour, Crude Cinnamon, and Their Combination on Glycemia, Dyslipidemia, and Adipose Tissue Hormones in Type 2 Diabetic Rats

Abstract: This study aimed to evaluate the effects of barley flour, crude cinnamon, and their combination on blood glucose, serum insulin, serum lipid profile, and serum adipose tissue hormones in streptozotocin-induced diabetic rats. Male Wistar rats (n=35) were divided into five groups: nondiabetic, diabetic, diabetic group fed 5% cinnamon, diabetic group fed 30% barley, and diabetic group fed 5% cinnamon and 30% barley. Fasting blood glucose, insulin, lipid profile, adiponectin, and leptin were measured after 8 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 46 publications
9
24
0
Order By: Relevance
“…Although cinnamon has anti‐diabetogenic effects, earlier studies support the hypothesis that this effect is, at least in part, independent of adiponectin stimulation . Previously, we reported that aqueous cinnamon extract supplementation promotes a reduction in leptin serum concentration and mRNA expression in WAT, which has been corroborated in other studies . However, during lactation, this effect of cinnamon appears to be nullified.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although cinnamon has anti‐diabetogenic effects, earlier studies support the hypothesis that this effect is, at least in part, independent of adiponectin stimulation . Previously, we reported that aqueous cinnamon extract supplementation promotes a reduction in leptin serum concentration and mRNA expression in WAT, which has been corroborated in other studies . However, during lactation, this effect of cinnamon appears to be nullified.…”
Section: Discussionsupporting
confidence: 81%
“…5,16 Previously, we reported that aqueous cinnamon extract supplementation promotes a reduction in leptin serum concentration and mRNA expression in WAT, 5 which has been corroborated in other studies. 42,43 However, during lactation, this effect of cinnamon appears to be nullified. Moreover, the normal serum leptin levels were in agreement with the unchanged food intake observed in the cinnamon-supplemented dams.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it activates transient receptor potential‐ankyrin receptor 1 (TRPA1) and genes involved in fatty acid oxidation in adipose tissue. Cinnamon might also stimulate interscapular brown adipose tissue and hyperinsulinemia, decrease serum leptin levels, regulate the expression of peroxisome proliferator‐activated receptor γ (PPARγ) and CCAAT/enhancer binding protein (C/EBPs) family, change the gut microbiota and markers of the gut barrier, and prevent adipocyte differentiation and adipogenesis (Camacho et al, ; Lee, Siaw, & Kang, ; Shatwan, Ahmed, & Badkook, ; Van Hul et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study, Shatwan et al 20 assessed the effect of cinnamon extract on feed intake of male Wistar rats. They were of the view that feed intake was significantly higher (35.99 ± 3.17 and 30.23 ± 3.58 g) in diabetic and cinnamon treated rats as compared to control (25.93 ± 1.33 g) group.…”
Section: Discussionmentioning
confidence: 99%